2021
DOI: 10.3390/s21248186
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of the Microsoft Kinect and Ambulatory Sensor-Based Motion Tracking Devices to Measure Shoulder Range-of-Motion: A Systematic Review and Meta-Analysis

Abstract: Advancements in motion sensing technology can potentially allow clinicians to make more accurate range-of-motion (ROM) measurements and informed decisions regarding patient management. The aim of this study was to systematically review and appraise the literature on the reliability of the Kinect, inertial sensors, smartphone applications and digital inclinometers/goniometers to measure shoulder ROM. Eleven databases were screened (MEDLINE, EMBASE, EMCARE, CINAHL, SPORTSDiscus, Compendex, IEEE Xplore, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 132 publications
0
13
0
1
Order By: Relevance
“…In such studies, the type of device may affect the reliability and validity of the measurement; thus, the present study will analyze results by device in subgroup analysis. Lee et al [24] reported that sitting and standing positions may cause differences in shoulder ROM measurements, and Beshara et al [4] emphasized appropriate patient posture and protocol standardization for measuring shoulder ROM. For these reasons, this study aims to analyze measurement methods that may affect validity and reliability, including patient and sensor location in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such studies, the type of device may affect the reliability and validity of the measurement; thus, the present study will analyze results by device in subgroup analysis. Lee et al [24] reported that sitting and standing positions may cause differences in shoulder ROM measurements, and Beshara et al [4] emphasized appropriate patient posture and protocol standardization for measuring shoulder ROM. For these reasons, this study aims to analyze measurement methods that may affect validity and reliability, including patient and sensor location in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, its low inter-rater reliability and measurement variability between clinicians make it difficult to apply in clinical settings. [4] Although a 3D-marker based motion tracking system is used as an alternative, it is expensive, requires a large space, and requires time and clinician’s experience. These drawbacks make traditional motion capture systems unsuitable for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 20 , 21 ], the measures of shoulder functional movements, provided by Kinect, have been compared with the measure given by clinical and digital goniometers and optoelectronic system with good results in terms of device reliability and validity. In a recent systematic review [ 22 ], the authors evidenced moderate to good levels of intra- and inter-rater reliability to measure shoulder’s ROM using different devices, such as smartphone applications, digital inclinometers/goniometers, inertial sensors, and Kinect.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Also, markerless motion capture systems have been validated and applied to functional diagnostics and rehabilitation. [6][7][8] The common commercially available sensors used for markerless motion analysis are Leap Motion Controller (LMC; Leap Motion Inc., San Francisco, USA) and consecutive versions of Microsoft Kinect sensors (Kinect for Windows v. 1 (V1) and Kinect for Windows v. 2 (V2); Microsoft Corp., Redmond, USA). 9,10 For center-based and home rehabilitation purposes, Nintendo Wii Mote, Wii Balance Board (Nintendo Inc., Redmond, USA) and Microsoft Kinect motion-sensing game controllers have gained popularity over the past years.…”
Section: Introductionmentioning
confidence: 99%